Socio-cultural, economic, and environmental implications for innovation in sustainable food in Africa - Assan, Never (Frontiers in Sustainable Food Systems, 2023)
The debate over innovation in sustainable food in Africa is multifaceted and complex since it is impacted by an array of issues, including social, cultural, religious, and environmental implications. The diversity of cultures on the continent, as well as religion, influence the foods that people eat. The architecture of agro-ecological zones influences food production and, as a result, the sort of innovation in sustainable food. Africa, in particular, has immense potential for the development of multiple sustainable food innovations, whether in terms of food, culture, or tradition. By sustainable food innovation, it may be possible to improve Africa's food systems from the demand side while also mitigating the effects of climate change. For Africa, it is the food crisis that simply cannot be allowed to go to waste, hence the need for innovation in sustainable food solutions in its own context. Africa’s long-standing food crisis, recently worsened by the COVID-19 pandemic and, increasingly, by climate change and heavily weighed on gender disparities in agriculture and food production, threatens to have dire consequences, especially on achieving the SDGs in Africa. Innovation in sustainable food is at the forefront of all Africa needs for its survival at every current stage of population evolution; this applies whether in industrialized or impoverished nations, rural or urban, village or metropolis, etc. It is false to believe that the only sources of innovation in sustainable food are cutting-edge research or the most recent developments in genomic science. The discussion gives an opinion on the socio-cultural, economic, and environmental factors and their implications for innovation in sustainable food in Africa.